A supply chain framework for characterizing indirect vulnerability - Gotangco, Charlotte Kendra Z (Archīum Ateneo, 2017)
Purpose Climate vulnerability assessments are often operationalized by the analysis of indicators defined by the spatial boundaries of the community under study. These, however, sometimes fail to capture interdependency among communities for basic resources. This paper aims to propose a framework for characterizing vulnerability caused by interdependency by adapting a supply chain lens. Design/methodology/approach The paper proposes a definition for “indirect vulnerability” that recognizes the transboundary and teleconnected nature of vulnerability arising from resource networks among cities and communities. A conceptual framework using a supply chain approach is presented for climate hazards in particular. This approach is then demonstrated through a rapid appraisal of the rice, energy and water supply chains and the waste management chains of Metro Manila. Findings The application of the supply chain lens to assessing the indirect vulnerability of Metro Manila brings to fore issues extending beyond the decision-making boundaries of local government units. Addressing these will require vertical government coordination and horizontal inter-sectoral collaboration. Thus, this supply chain-based indirect vulnerability assessment can be complementary to traditional vulnerability assessments in providing a larger systems perspective. Originality/value Innovative tools are needed to make community vulnerability assessments both holistic and tractable. Existing methods in the private sector can be adapted rather than reinventing the wheel. This supply chain framework can be a useful decision support and planning tool across governance levels to comprehensively address vulnerability.